2015
DOI: 10.4103/0974-7796.158503
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous pyelonephritis: Is nephrectomy warranted?

Abstract: Introduction:Emphysematous pyelonephritis (EPN) is associated with high mortality rate, up to 25%. There is still conflicting reports regarding the most appropriate management, conservative versus nephrectomy.Objective:To describe the outcome of patients with EPN.Methods:We retrospectively reviewed the medical records of patients diagnosed with EPN by computed tomography from three tertiary institutes in Jeddah, Saudi Arabia. Type of management was classified as conservative and surgical. The conservative incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In our patients, we observed that the bacteria were sensitive to piperacillin-tazobactam and meropenem in most patients, while they were resistant to gentamicin and levofloxacin in many patients. The success of conservative management has been reported in small case series and few case reports [ 21 25 ]. We found that PCD or DJ stenting, as the preferred initial treatment was helpful in our patients with EPN.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, we observed that the bacteria were sensitive to piperacillin-tazobactam and meropenem in most patients, while they were resistant to gentamicin and levofloxacin in many patients. The success of conservative management has been reported in small case series and few case reports [ 21 25 ]. We found that PCD or DJ stenting, as the preferred initial treatment was helpful in our patients with EPN.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article “Emphysematous pyelonephritis: Is nephrectomy warranted?” by Alsharif et al . [ 1 ] This article highlights interesting updates in managing emphysematous pyelonephritis (EPN) from radical surgery to medical management. Similar finding was published earlier by Ubee et al .…”
mentioning
confidence: 99%
“…The results clearly shown that both patients who undergo early nephrectomy had lower hemoglobin (Hb) level (7.1 and 7.4 g/dl), whereas others had Hb range between 9.1 and 13.1 mg/dl. [ 1 ] As Hb levels usually determine the chronicity of the disease, there was a possibility that both patients had late detection. Besides that, there were three patients developed septic shock in this series.…”
mentioning
confidence: 99%
See 2 more Smart Citations